Is labour market discrimination against ethnic minorities better explained by taste or statistics? A systematic review of the empirical evidence - Louis Lippens; Stijn Baert; Abel Ghekiere; Pieter-Paul Verhaeghe; Eva Derous (Global Labor Organization (GLO), 2020)
Scholars have gone to great lengths to chart the incidence of ethnic labour market discrimination. To effectively mitigate this discrimination, however, we need to understand its underlying mechanisms because different mechanisms lead to different counteracting measures. To this end, we reviewed the recent literature that confronts the seminal theories of taste-based and statistical discrimination against the empirical reality. First, we observed that the measurement operationalisation of the mechanisms varied greatly between studies, necessitating the development of a measurement standard. Second, we found that 20 out of 30 studies examining taste-based discrimination and 18 out of 34 studies assessing statistical discrimination produced supportive evidence for said mechanisms. However, (field) experimental research, which predominantly focuses on hiring outcomes, yielded more evidence in favour of taste-based vis-à-vis statistical discrimination, suggesting that the taste-based mechanism might better explain ethnic discrimination in hiring.
Keywords: 330; taste-based discrimination; statistical discrimination; ethnicity; race; labour market; systematic review